Variación demográfica y geográfica de los coeficientes de máximos consumos diarios de agua potable en 50 poblados ecuatorianos - Valiente Cuchipe, Bryan Leandro (2022)
ABSTRACT: The demand for drinking water responds to consumption needs, customs, weather dynamics and the constant adaptation to the development conditions of each town. The current design standard CPE INEN 005-9-1 establishes limit values for the control of this variability in Ecuadorian populations, whose recommendations date back to the 1970s without significant changes to date. This work is based on the analysis of 12 previous investigations on the value of the coefficient of variation Kd in 50 Ecuadorian towns, to compare them with the values of the standard. The variation is associated with the historical behavior of drinking water consumption for populations of less than 150,000 inhabitants in the residential sector, located in the Sierra and Amazon regions of the country. The database was organized and manually cleaned according to the geographic regions and demographic ranges identified in the study. The statistical analysis established relationships between the variation in drinking water consumption and population size. Significant differences were identified between the Kd coefficient values by demographic ranges and the single limit values considered in the standard. The results show the variability of consumption according to population size; there are towns that require higher Kd coefficient values than the normative ones. It would be advisable to make use of the information provided in future designs (expansions or new drinking water projects) since it is specific to each population.